Interpreting Estonian Demonstratives: The Effects of Referent’s Distance and Visual Salience - Reile, Maria; Averin, Kristiina; Põldver, Nele (Frontiers in Psychology, 2020)
Most of the research done with spatial demonstratives (words such as this, here and that, there) have focused on the production, not the interpretation, of these words. In addition, emphasis has been largely on demonstrative pronouns, leaving demonstrative adverbs with relatively little research attention. The present study explores the interpretation of both demonstrative pronouns and demonstrative adverbs in Estonian—a Finno-Ugric language with two dialectal-specific demonstrative pronoun systems. In the South-Estonian (SE) dialectal region, two demonstrative pronouns, see—“this” and too—“that”, are used. In the North-Estonian (NE) region, only one, see—“this/that”, is used. The aim of this study is twofold. First, we test if the distance and the visual salience of a referent have an effect on the interpretation of demonstratives. Second, we explore if there is a difference in the interpretation of demonstratives between native speakers from SE and NE. We used an interpretation experiment with 30 participants per group (total n = 60) and compared the SE and NE group responses. The results clearly show that the distance of the referent has an effect on how demonstratives are interpreted across the two groups, while the effect of visual salience is inconclusive. There is also a difference in the interpretation of demonstratives between the two dialectal groups. When using the Estonian with an influence of the SE dialect, the NE speakers rely on demonstrative adverbs in interpreting the referential utterance that includes demonstrative pronoun and adverb combinations, whereas the SE speakers also take into account the semantics of demonstrative pronouns. We show that, in addition to an already known difference in the production, there is also a difference in the interpretation of demonstratives between the two groups. In addition, our findings support the recognition that languages that have distance neutral demonstrative pronouns enforce the spatial meaning of a referring utterance by adding demonstrative adverbs. Not only is the interpretation of demonstrative pronouns affected, but the interpretation of demonstrative adverbs as well. The latter shows the importance of studying adverbs also, not just pronouns, and contributes to further knowledge of how demonstratives function.